Effects of Phytase and Vitamin D3 addition to Diets Containing Distillers Dried Grains with Solubles (DDGS) on Performance and Some Egg Traits in Laying Hens - Koksal , Bekir Hakan; Sacakli, Pinar; Ergun, Ahmet (International Journal of Poultry Science, 2012)
The effects of feeding diets containing 15% Distillers Dried Grains with Solubles (DDGS) with or without phytase or vitamin D3 on egg production and some quality parameters were evaluated in laying hens. At 40 wks of age, 324 Lohmann Brown hens were randomly assigned to 6 treatments (two positive and two negative controls and two treatments) with 9 replicate groups of 6 hens each. The diets were formulated to be isocaloric and isonitrogenous (17% CP and 2700 kcal/kg ME, respectively). Dietary treatments consisted of two positive control which contain with or without 15% DDGS (3.5 g Available Phosphorus (AP)/kg and 3.58 g Ca/kg diet) in diets; two negative control which contain with/without 15% DDGS (1.9 g AP/kg and 3.33 g Ca/kg diet) in diets; negative control diet containing 15% DDGS supplemented with 300 FTU phytase/kg diet or phytase + 0.06% vitamin D3, respectively. At the end of the experiment period, dietary treatments did not significantly affect egg production, feed intake, feed efficiency and some egg quality parameters. However, hens fed with 15% DDGS consumed significantly higher yolk color then other treatment groups (p<0.001). As a result, 15% DDGS addition had no adverse effects on performance and egg quality parameters in laying hens.